1977
DOI: 10.1107/s0567739477000989
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Fankuchen effect in neutron diffraction by curved crystals

Abstract: Experimental evidence of the Fankuchen effect for neutron diffraction by curved crystals is presented and discussed. The Fankuchen effect consists of a space condensation of neutrons (or X-rays) diffracted by an asymmetrically cut crystal. Theoretical considerations are presented on the Fankuchen effect in the case of ideal mosaic crystals, perfect crystals and ideal curved crystals. This analysis shows that mosaic crystals behave quite differently from perfect crystals. Whereas for perfect crystals the asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…This arrangement may be used in the large cross section of the incident polychromatic beam and enables us to obtain a high monochromatic beam density. The effect of the spatial condensation of neutrons because of asymmetric Bragg diffraction [originally used by Fankuchen (1937) with a X-ray beam] by elastically bent crystals was first studied in the paper of Albertini, Boeuf, Lagomarsino, Mazkedian, Melone & Rustichelli (1977). Here the authors reported a considerable gain (of about four) in the neutron current density in comparison with the case of the symmetrically cut crystal for ct = 26, fl = 6 °, 2 = 0"18 nm and Si 111 reflection.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…This arrangement may be used in the large cross section of the incident polychromatic beam and enables us to obtain a high monochromatic beam density. The effect of the spatial condensation of neutrons because of asymmetric Bragg diffraction [originally used by Fankuchen (1937) with a X-ray beam] by elastically bent crystals was first studied in the paper of Albertini, Boeuf, Lagomarsino, Mazkedian, Melone & Rustichelli (1977). Here the authors reported a considerable gain (of about four) in the neutron current density in comparison with the case of the symmetrically cut crystal for ct = 26, fl = 6 °, 2 = 0"18 nm and Si 111 reflection.…”
Section: Introductionmentioning
confidence: 76%
“…As in the paper of Albertini, Boeuf, Lagomarsino, Mazkedian, Melone & Rustichelli (1977), let us assume that the regions of the acceptance angles 6oOs and 6o0" corresponding to both geometries are equal. By means of (3) …”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out that one does not expect a loss in the diffracted intensity due to asymmetry as should occur in the case of perfect crystals because the integrated reflectivity of elastically deformed crystals does not depend on the angles between the crystal surface and the incident and reflected beam directions but on the angle between the scattering vector h and the vector of the local displacement of atoms u (Takagi, 1969;Albertini, Boeuf, Lagomarsino, Mazkedian, Melone & Rustichelli, 1977).…”
Section: Theoretical Backgroundmentioning
confidence: 99%